Fuzzy Logic Evaluation of Water Quality Classification for Heavy Metal Pollution in Karasu Stream, Turkey - Kaya, Hasan; Sonmez, Adem Yavuz; Hisar, Olcay; Aras Mehan, Hatice Nur; Hasiloglu, Samet (Cevre Koruma ve Arastirma Vakfi, 2013)
Traditional water quality evaluation methods use discrete form that involve upper and lower limits, and the concentrations values are equally important when the values are near to or far away from the limits. Moreover, each quality parameter might belong to one of the four classes; therefore differences of the classes of the parameters may be vagueness. In this study, an index model is purposed for quality evaluation of water quality classification using fuzzy logic. For that purpose, a data set (12 months, total 180 measurements) about several heavy metals such as Copper (Cu), Zinc (Zn), Manganese (Mn), Lead (Pb), Nickel (Ni), Cadmium (Cd) and Iron (Fe) was collected from 5 monitoring stations in Karasu River. After that, fuzzy logic assessment method was used to quality evaluation for heavy metal pollution in Karasu stream. In conclusion, it was supposed that fuzzy logic evaluation method may also be used as an alternative tool for decision-making in environmental management.
Keywords: 13. Climate action; 14. Life underwater; 6. Clean water